(3QhVI GdYdeGA aj JGQjN GdMceGAs - (3Ydj Hf jhSa Hf EHQGgje GdTjHGfj GdbaWj, CHh GdMSf, LeGd GdOjf,J (B646 (3g` s
(3BNQgG (B:s
(3BNQ eGh LO ef GdefJbj ef JGQjN GdMceGA , JCdja SjOi GdLO GdCYXe LeGd GdOjf Ydi Hf jhSa Hf EHQGgje GdbaWi s
(3GdfGSN CMeO CMaGO GdeDdas
(3hgPG GdcJGH GdeWHhY HYfhGf (B: (3ENHGQ GdYdeGA HCNHGQ GdMceGAs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B263s
Keywords: (3GdJGQjNs